Matching Design and Simulation Analysis for Two-speed Transmission of Electric Vehicle - Yu Chen; Kun Yang; Jiaming Zhou; Yong Fang; Youtang Wang; Jie Wang (Jixie chuandong)
Based on AVL Cruise， the powertrain matching design and simulation for the direct drive scheme and the two-speed transmission scheme are carried out. According to the matching results， the two-speed transmission is structurally designed， including parameters calculation of key parts， static analysis and modal analysis. By comparing the current， the torque and the battery current of two schemes under various working conditions， the influence of the two-speed transmission on the economy and dynamic of the whole vehicle is clarified. The results show that， key parts meet the strength requirements under various working conditions and resonance is not occurred. The two-speed transmission scheme can reduce the demand for the drive motor torque and peak current， improve the system efficiency， which can improve the vehicle's economy and increase the driving range effectively. The related research can provide a reference for the selection of the electric vehicle power transmission system.